Reproductive biology, ecology and historic biogeography of selected rare and endagered Oxalis L. (Oxalidaceae) species - Zietsman, Johlene (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2007.